If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 5(t + -1) + -4t = 0 Reorder the terms: 9 + 5(-1 + t) + -4t = 0 9 + (-1 * 5 + t * 5) + -4t = 0 9 + (-5 + 5t) + -4t = 0 Combine like terms: 9 + -5 = 4 4 + 5t + -4t = 0 Combine like terms: 5t + -4t = 1t 4 + 1t = 0 Solving 4 + 1t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 1t = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 1t = 0 + -4 1t = 0 + -4 Combine like terms: 0 + -4 = -4 1t = -4 Divide each side by '1'. t = -4 Simplifying t = -4
| 2(6x-3)=6(3-2x) | | -10n*2-5(3-n)(2n+11)=-30 | | 7(t-9)+5-t= | | -(x-4)=2x+x | | 20x+16=180 | | 4t-9+6(2t-9)= | | 125p^2-200p+80=0 | | [10+3c]-15=-5 | | 3+5(5t-1)-8t= | | 3x^4-24=0 | | 2x+-18=2 | | 8x^2-96x=0 | | (8+2i)(4-3i)= | | 2x+-19=2 | | 2x+-21=2 | | 2x+22=-2 | | 2x+-22=2 | | 2(3x+5x)+17=13x+20 | | (-7-2i)+(-5-3i)= | | 3(2x+1)=6(2x+3)+3 | | 5(33333333p-555555)=22 | | (2w^3+4x^2+5)+(3w^3+w^2+4w)= | | x(x+1)(x+2)(x+3)(x+4)(x+5)(x+6)(x+7)(x+8)(x+9)(x+10)(x+11)=0 | | x^2+x-26=4 | | 9a(3+2a)-5a= | | x(x+1)(x+2)(x+3)(x+4)(x+5)(x+6)(x+7)(x+8)(x+9)(x+10)=x+1 | | 8k^2+40k+50=0 | | 2=5x^5-2x^2 | | 7n+17m=191 | | 24x(4+12)=4 | | 8n*2-2(2n-7)(2n+6)=11n | | 9x+-6y=18 |